Analisis Kebutuhan Sumber Daya Audit Sistem Informasi Menggunakan COBIT 2019 pada PT. XYZ - Wiryadinata, Doni; Barid, Aziz Jihadian; Nugraheni, Dinar Mutiara Kusumo (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
An Information Systems Audit using the COBIT 2019 framework identifies 40 governance and management objectives that must be analyzed, to find gaps in the relative importance of information systems governance based on the COBIT 2019 principles. The large scope of the audit scope, can result in a less focused audit process , protracted, as well as audit financing that is not effective and efficient. Therefore, a method is needed in a quantitative approach to determine the priority scale in each process in order to produce an effective and efficient audit. In determining the priority scale in this study, it is done by analyzing the time, number of personnel and costs needed to complete the audit work. Analysis of audit time requirements is carried out by estimating the number of effective working hours (6.5 hours/day) and the number of days needed to evaluate processes, organizational structure and matters related to the organization's business process flow; analysis of personnel needs is carried out by adjusting the level of complexity of audit problems with the competence of the auditor; while the cost analysis is done by estimating the cost standard with the number of days needed. From the results of this analysis, the time required to complete the audit at PT. XYZ, namely for 10 working days, with the need for auditor personnel as many as 10 people, and the cost of personnel needs of IDR111.500.000,00.